Tribos urbanas e suas práticas religiosas: o surgimento de uma teologia contextual. - Campos, Márcio Gonçalves (2019)
This paper aims to analyze the possible development of a contextual theology in the punk environment as a challenge for the dialogue of the Churches with the urban tribes in their most diverse interfaces. Urban tribes are: microgroups that make up subcultures imbued with a sense of belonging that apply a specific ethic among themselves, promoting and participating in a large network of communication within and outside the microgroups and ghettos. From the perspective of the objective, bibliographic research and seven sites on Christian punks were conducted. For data collection, semi-structured interviews were conducted with ten people who met the following criteria: being openly Christian; have some involvement with the Christian punk-underground scene and participate in some faith community, which may be traditional or alternative / underground. As theoretical basis were the authors: Maffesoli (1998), Berger and Luckmann (2004), Bivar (2001), Hiebert (2010) and Nicholls (year). The survey finds that urban tribes arise from the phenomenon generated by the advent of paradigm shifts, meaning crises in the mid-1950s, 60s, 70s. As far as Christian and secular punks are concerned, it was evident that among the existing urban tribes , punks are the most diverse urban tribe in the way of thinking, authentic in their music, attitudes and unique in their originality, in their way of being and dressing. Research points out that joining hardcore punk rock does not make it impossible for a person to have a genuine relationship with Jesus through their faith, that is, without losing the Christocentric content. Concerning the mission of the Churches among the urban tribes, the research reveals the need for the resignification of the evangelistic and missional meaning of the Church, which needs to adhere to the changes of paradigms that produce a new profile of people in the most diverse contexts. Based on the results, we affirm that love is the most perfect way to act with any human being, regardless of the tribe to which they belong.